2016
DOI: 10.1021/acs.est.6b04280
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hydrophilicity and Mechanical Properties of Nanocomposite Membranes with Cellulose Nanocrystals and Carbon Nanotubes

Abstract: The inherent properties of hydrophilicity and mechanical strength of cellulose nanocrystals (CNCs) make them a possible alternative to carbon nanotubes (CNTs) that may present fewer objections to application water-treatment membranes. In this work, the hydrophilicity and mechanical properties of CNCs and CNTs nanocomposite poly(ether sulfone) (PES) membranes were characterized and compared. Membrane pore geometry was analyzed by scanning electron microscopy (SEM). Overall porosity and mean pore radius were cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(47 citation statements)
references
References 59 publications
3
44
0
Order By: Relevance
“…The composite membrane exhibited ultrahydrophobic and superoleophilic properties with water and oil contact angles being 144.2 AE 1.2 and 0 , respectively. They reported that the wettability of the coated composite membrane is resistant to elevated temperature (up to 350 C) and stable towards a wide range of pH values (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Thus, such wetting behavior allowed the membrane to be applied as a substrate for separation of free water and oil.…”
Section: Carbon Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…The composite membrane exhibited ultrahydrophobic and superoleophilic properties with water and oil contact angles being 144.2 AE 1.2 and 0 , respectively. They reported that the wettability of the coated composite membrane is resistant to elevated temperature (up to 350 C) and stable towards a wide range of pH values (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Thus, such wetting behavior allowed the membrane to be applied as a substrate for separation of free water and oil.…”
Section: Carbon Nanofibersmentioning
confidence: 99%
“…2 In order to separate much smaller oil droplets effectively from stable oil-water emulsion numerous studies have been performed to design advanced functional nanomaterials and membranes for oil/water separation. [2][3][4][5][6][7][8][9][10][11][12] However, the complicated issues regarding the valuable oil recovery and recycled use of nanomaterials have to be considered in the point of economic view. 13,14 Membrane technology on the other hand has been acknowledged as an advanced separation process of surfactant-stabilized emulsions, with allowable discharge quality and a relatively simple process from an operational viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks around 1000 cm −1 and 1600 cm −1 were ascribed to the C-O-C vibration and the carbonyl functional groups of cellulose [22][23][24]. For the spectra of neat CNTs, the characteristic absorption around 1640 cm −1 was assigned to the quaking of the carbon skeleton [25,26]. For the spectra of TOCNFs, the peaks at 1430 cm −1 and 1325 cm −1 were assigned to the hydrogen bonding and CH 2 wagging [27].…”
Section: Dispersion State and Chemical Analysis Of Tocnf-cnt And Tocnmentioning
confidence: 99%
“…Notably, the literature shows that the addition of hydrophilic CNCs and CNTs may increase the rate of demixing by increasing the thermodynamic instability, leading to the membranes with higher porosity, pore radius, and surface porosity. [46] Higher hydrophilicity additives would be expected to result in a larger porous network. This observation is in accordance with the hypothesis that SiO 2 addition leads to the increased pore network modification developed in the previous section (Figure 4f,i.…”
Section: Membrane Morphologiesmentioning
confidence: 99%